2013
DOI: 10.1158/2159-8290.cd-12-0537
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Genomic Characterization of Oral Squamous Cell Carcinoma Identifies Frequent Somatic Drivers

Abstract: The survival of patients with oral squamous cell carcinoma (OSCC) has not changed significantly in several decades, leading clinicians and investigators to search for promising molecular targets. To this end, we performed comprehensive genomic analysis of gene expression, copy number, methylation and point mutations in OSCC. Integrated analysis revealed more somatic events than previously reported, identifying four major driver pathways (mitogenic signaling, Notch, cell cycle, TP53) and two additional key gene… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
554
2
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 492 publications
(595 citation statements)
references
References 44 publications
37
554
2
2
Order By: Relevance
“…Interestingly, the p.R88Q mutation identified in one of our HPV-positive samples (HPV?_4) was found in one tumor in the TCGA dataset, a HPVpositive sample (ID# TCGA-CR-6471) that also had a p.M1043V mutation. The p.R88Q (COSM746) and p.M1043V (COSM12591) have been reported in other cancers [27,28], but to the best of our knowledge, not as co-occurring in a HNSCC tumor. There was no evidence of the p.M1043V mutation in our HPV?_4 specimen, and therefore the p.R88Q may be recurrent in a minor population of HPV-positive tumors.…”
Section: Mutation Profilingmentioning
confidence: 67%
See 1 more Smart Citation
“…Interestingly, the p.R88Q mutation identified in one of our HPV-positive samples (HPV?_4) was found in one tumor in the TCGA dataset, a HPVpositive sample (ID# TCGA-CR-6471) that also had a p.M1043V mutation. The p.R88Q (COSM746) and p.M1043V (COSM12591) have been reported in other cancers [27,28], but to the best of our knowledge, not as co-occurring in a HNSCC tumor. There was no evidence of the p.M1043V mutation in our HPV?_4 specimen, and therefore the p.R88Q may be recurrent in a minor population of HPV-positive tumors.…”
Section: Mutation Profilingmentioning
confidence: 67%
“…With several highly cited genomic studies in head and neck tumors and a soon to be released TCGA study, it is clear that there is an opportunity to identify mutation, copy number and differential gene expression in these tumors to better inform treatment and prognosis than by HPV status alone [27][28][29][48][49][50][51]. The mutational spectrum shown in the HPV-negative tumors of this small study demonstrated a high mutational burden in these tumors and a source of potential difficulty in interpreting and reporting using exome or many ([100) gene diagnostic panels which could yield hundreds or thousands of variant calls.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of Notch signaling by expressing full‐length NOTCH1 or its activated form ICN in human OSCC or HNSCC cell lines leads to cell growth arrest 9, 27, 60. Consistently, inhibition of NOTCH activation promoted tumor growth in a HNSCC cell line harboring wild‐type NOTCH1[ 27], whereas activation of NOTCH1 resulted in reduced tumorigenicity in a mouse cancer model 9, 27 .…”
Section: Notch Signaling In Head and Neck Squamous Cell Carcinoma (Hnmentioning
confidence: 95%
“…Activation of Notch signaling by expressing full‐length NOTCH1 or its activated form ICN in human OSCC or HNSCC cell lines leads to cell growth arrest 9, 27, 60. Consistently, inhibition of NOTCH activation promoted tumor growth in a HNSCC cell line harboring wild‐type NOTCH1[ 27], whereas activation of NOTCH1 resulted in reduced tumorigenicity in a mouse cancer model 9, 27 . Similarly, it was reported that Notch inhibition can promote transdifferentiation of normal esophageal squamous epithelial cells toward a BE (Barrett's esophagus, a precursor of esophageal adenocarcinoma)‐like metaplasia 61.…”
Section: Notch Signaling In Head and Neck Squamous Cell Carcinoma (Hnmentioning
confidence: 95%
See 1 more Smart Citation